A relação histórica entre democracia e liberalismo. Um diálogo crítico com Norberto Bobbio - Scavo, Davide Giacobbo (2013)
This work seeks to examine the historical relationships established between liberalism and democracy, questioning the apparent inseparability between the two ideologies. Methodologically construct a hypothetical dialogue with the Italian thinker Norberto Bobbio, one of the most important systematizers of liberal democracy, defending a theoretical and conceptual complementarity between the two ideologies. Following the Bobbio theoretical propose, it presents the political contributions of classical liberalism that the Italian thinker identify as logical and axiological antecedent of the modern democracy, naturalizing and universalizing the principles and ideals of classical liberalism. Going counter, it problematizes the political contributions of classical liberalism, emphasizing the tension between liberal theory and its practice, between the declared political principles and their translation into concrete historical reality, reserving rights and freedoms to property minority and severe restrictions to the majority. The critical analysis of classical liberalism allows questioning the privilege position that Bobbio reserves to the liberalism in the democracy history, to restore the important contribution of illiberal politics currents in the civil, political and social rights history, advocating the democracy with its social character, inclusive and participatory